PERANCANGAN SISTEM INFORMASI COMPLAINT MANAGEMENT DENGAN METODE RAD MENGGUNAKAN FRAMEWORK LARAVEL - Abdussalaam, Falaah; Saputra, Samdea Anggieta (Politeknik Dharma Patria Kebumen, 2018)
This study aims to determine the complaint management system that is running in PT Andalan Teknologi Mandiri, to know the obstacles and how to overcome the constraints of complaint management system problems. From the results of research that has been obtained, it turns out that the main obstacle of complaint management system in PT Andalan Technology Mandiri is the handling of customer complaints have not recorded either manually any computerized. Where the data handling complaints is needed by the company to meet ISO 9001 company standards. method of designing information systems using UML modeling (Unified Modelling Language) then implemented using web-based programming language framework Laravel with integration MySQL database applications. Then the software development method used is RAD (Rapid Application Development). The suggestions provided are: 1) required system administrator to manage complaint management information system 2) application made can be developed from the side of notification using email and SMS gateway to facilitate customer, engineer, and administrator get progress ticket information made.